Effects of ripeness and extraction conditions on the content of phenolic compounds in banana peels (Musa paradisiaca L.) - Pham, T. N. (2024)
The banana peels accounts for approximately 36% of the total fruit weight yet are mostly discarded as waste or used only for animal feeding. However, studies have shown that this by-product is rich in phenolic compounds and is a traditional treatment. The levels and composition of phenolic compounds are influenced by various factors. The purpose of the present study was to evaluate the effect of ripeness and extraction conditions on polyphenol content and antioxidant activity of banana peels (Musa paradisiaca L.) by analysing the total phenolic content (TPC) and using 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging assays. Results have shown that yellowish green coloured banana peels exhibited significantly higher antioxidant activity as compared to mature (green-coloured) and ripe (yellow-coloured) peels. The optimal extraction conditions include ethanol concentration of 50%, material/solvent ratio of 1:40 (w/v), extraction time of 1.5 hrs and temperature of 60°C. Under these conditions, the obtained TPC and the antioxidant activity was approximately 9.93 mg GAE/g and 50 μmol TE/g, respectively. Quantitative results by HPLC indicate the presence of quercetin-3-glc, vanillic acid, caffeic acid, ferulic acid, gallic acid and epicatechin.